EFEK KEJUT PANDEMI COVID-19 PADA KINERJA BANK PERKREDITAN RAKYAT (BPR): STUDI PADA KARESIDENAN SEMARANG - Pratiwi, Ririh Dian (Faculty of Economic and Business Universitas STIKUBANK, 2022)
The Covid-19 pandemic has had an impact on various sectors of life, including a shock effect for the banking industry. The decline in bank credit growth in mid-2020 is evidence of the shock effect. To anticipate various effects, the central bank supports the government by issuing various policies. BPR is growing rapidly in both urban and rural areas. BPR is seen as able to directly touch the community and small business owners with various financial activities. However, at the beginning of the COVID-19 pandemic, OJK recorded a very high credit restructuring value. Similar conditions were also experienced by BPRs in the Residency of Semarang. This study aims to determine whether there is a difference (which is a shock effect) in the financial performance of BPR before and during the covid-19 pandemic. The sample obtained by purposive sampling method is as many as 62 BPR located in the Residency of Semarang. This study uses secondary data in the form of quarterly BPR financial reports. Financial performance analysis was carried out using the CAMEL method. As a result, financial performance in terms of the capital ratio (CAR) and liquidity ratio (LDR) was proven to be affected by the shock effect of the COVID-19 pandemic because there were significant differences between before and during the COVID-19 pandemic. Financial performance in terms of asset quality, management ratios and income, each of which is measured by the ratio of NPL, ROA and BOPO, it is proven that there is no difference between before and during the covid-19 pandemic.